2020
DOI: 10.1186/s12887-020-02349-6
|View full text |Cite
|
Sign up to set email alerts
|

Hypoketotic hypoglycemia in citrin deficiency: a case report

Abstract: Background Citrin deficiency (CD) is a recessive metabolic disease caused by biallelic pathogenic variants in SLC25A13. Although previous studies have reported ketosis in CD, it was observed at the time of euglycemia or mild hypoglycemia. Blood ketone levels concomitant with symptomatic or severe hypoglycemia in CD have not been a topic of focus despite its importance in identifying the etiology of hypoglycemia and assessing the ability of fatty acid utilization. Herein, we describe a patient with CD who had r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…On the basis of our findings and those of previous studies, we should consider citrin deficiency when individuals experience severe hypoglycemia in childhood. 17,18 This report included nine patients with symptomatic hypoglycemia, which might indicate failed glucose homeostasis due to citrin deficiency. These attacks were recorded during a catabolic state after 1 year of life but never in infancy, except in neonates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the basis of our findings and those of previous studies, we should consider citrin deficiency when individuals experience severe hypoglycemia in childhood. 17,18 This report included nine patients with symptomatic hypoglycemia, which might indicate failed glucose homeostasis due to citrin deficiency. These attacks were recorded during a catabolic state after 1 year of life but never in infancy, except in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, there have been few reports on the symptoms of or diagnostic approaches for citrin deficiency in childhood. 5,[15][16][17][18] Chong et al reported a characterization of citrin deficiency and that two patients were diagnosed after 1 year of age by family screening the siblings of NICCD infants. 16 Of the two patients, one presented growth failure, and the other had no symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The symptoms of NICCD include prolonged jaundice, cholestatic liver injury, and growth retardation. After NICCD, obvious symptoms seem to disappear during childhood, but hypoglycemia is frequently noted, especially with hypoketosis or growth failure [6] , [7] . Adult-onset type II citrullinemia can manifest as hyperammonemia and encephalopathy in adulthood [8] .…”
Section: Introductionmentioning
confidence: 99%